Clinical and pharmacoeconomic profile of lanthanum carbonate treatment of hyperphosphataemia in chronic renal dialysis patients - Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2010)
Hyperphosphatemia is recognized as a principal mineral disorder in chronic kidney disease (CKD) that leads to the development of secondary hyperparathyroidism. Approximately 70% of patients with end-stage renal disease (ESRD) and dialysis have hyperphosphataemia, which is associated with renal osteodystrophy, metastatic calcification and increased mortality and morbidity. Despite dietary restriction and dialysis, most patients will require a phosphate-binding agent to treat this condition.Lanthanum carbonate is an new, potent, selective, no-resin, non-calcium phosphate binder that retains high affinity for phosphate over a wide pH range, does not bind bile acids or contribute to metabolic acidosis. Taken with food, it is well tolerated. It is poorly absorbed and does not require functioning kidneys to be removed from the body. There is no evidence from current studies that it accumulates to biologically significant levels in tissues. Lanthanum carbonate has been shown in clinical studies of up to 6 years to be an effective, well-tolerated phosphate binder. Lanthanum carbonate controls hyperphosphataemia without increasing calcium intake above guideline targets and has the potential to reduce pill burden and increase patient compliance compared with other phosphate binders. Reported adverse effects are mainly gastrointestinal, and do not differ from those of calcium carbonate. The new phosphate binders, lanthanum carbonate and sevelamer, have increased the possibilities for serum phosphate control, at the expenses of significant increases in costs. The cost-effectiveness of lanthanum carbonate has been assessed by three different studies. A recent analysis, conducted on the perspective of the UK NHS, shows it is cost-effective to follow current treatment guidelines and treat all patients who are not adequately maintained on calcium carbonate (serum phosphorus above 5.6 mg/dl) with second-line lanthanum carbonate. This is particularly the case for patients with serum phosphorus above 6.6 mg/dl. A retrospective analysis, performed on IHCSI data base (USA), and a prospective study conducted in Spain show that lanthanum carbonate is cost-effective as compared with sevelamer, requiring less number of tablets, a fact that might improve adherence, and that probably explains better results with lower costs.